TINJAUAN YURIDIS TERHADAP PENUNDAAN ATAU PENGHENTIAN JAMINAN SOSIAL PADA PERPRES NOMOR 14 TAHUN 2021 - Dodi Hidayat; Rahmawati Kusuma (Fakultas Hukum Universitas Mataram, 2021)
The purpose of this study is to find out how administrative sanctions are regulated in Presidential Regulation Number 14 of 2021 and to find out the basis for consideration of Presidential Regulation Number 14 of 2021. The method used is normative research method. The research results show that Presidential Regulation Number 14 of 2021 contradicts with higher regulations, namely the National Social Security System Law, Human Rights Law, and the Constitution. The basis considerations for the issuance of Presidential Decree No. 14 of 2021 are the need for the procurement of COVID-19 vaccines, the scope of force majeure, follow-up events after the implementation of vaccinations, and an advance payment or down payment for the provision of COVID-19 vaccine. Furthermore, to improve economic stability as the legal basis for the issuance of the Presidential Regulation Number 2 of 2020.